Securitization Versus Accommodation: A Theoretical Review of Nigerian State Responses to Biafra Agitation (2010–2023) - Clement Audu Alu (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
The resurgence of Biafra secessionist agitation constitutes a significant challenge to Nigeria’s national integration and state legitimacy. This article interrogates the divergent conflict management strategies adopted under the administrations of Goodluck Jonathan (2010–2015) and Muhammadu Buhari (2015–2023). Drawing on Securitization Theory and Consociationalism, the study examines the transition from a non-kinetic, accommodative approach to a security-centric framework. The analysis demonstrates that while Jonathan’s strategy of elite inclusion generated short-term stability, it failed to address the structural drivers of separatist mobilization. In contrast, the Buhari administration’s securitized framing of the agitation as an existential threat contributed to its radicalization and organizational consolidation. The article argues that sustainable stability requires a hybrid conflict management framework that integrates de securitization, institutionalized dialogue, and structural governance reform aimed at restoring state legitimacy.